2017
DOI: 10.1016/j.toxlet.2017.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic effects of tartrazine (E 102) after systemic exposure are independent of oestrogen receptor interactions in the mouse

Abstract: HighlightsSystemic exposure to tartrazine results in hepatic periportal recruitment of inflammatory cells, increased serum alkaline phosphatase activity and mild hepatic periportal fibrosis.Tartrazine, its sulphonated metabolites and a common contaminant of the food additive do not interact with murine oestrogen receptors.Systemic exposure does not have an oestrogenic effect in mouse in vivo.Tartrazine, its sulphonated metabolites and a common contaminant of the food additive inhibited sulphotransferase, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…The food additive dye, TZ, induced oxidative stress in the liver and brain [3][4][5], altered learning and memory functions [12], and triggered neurobiochemical alterations [22] in adult rodents. In this study, we investigated the effect of perinatal exposure to TZ on the mice newborns, focusing on the behavioral alterations and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The food additive dye, TZ, induced oxidative stress in the liver and brain [3][4][5], altered learning and memory functions [12], and triggered neurobiochemical alterations [22] in adult rodents. In this study, we investigated the effect of perinatal exposure to TZ on the mice newborns, focusing on the behavioral alterations and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Given their attractive coloring properties, variable hues, stability, and low cost, approximately eight million tons of the synthetic food colorants are produced every year [2]. The azo dyes have been receiving significant consideration since these synthetic agents can pose a health risk and exert negative effects on the liver, kidney, and nervous system [3][4][5][6]. Recent reports have pointed to the ability of azo dyes to elicit oxidative stress [4,5] and pro-inflammatory effects [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a significant rise in the mean liver weight and congested blood vessels and areas of hemorrhage in the liver were not confirmed (Himri et al, 2011). Meyer et al (2017) found that initial systemic administration of tartrazine in mice resulting in a periportal recruitment of inflammatory cells, raised serum alkaline phosphatase activity and mild periportal fibrosis. Moreover, Tartrazine alone induced the colon and hepatic NF-κB activities but there was no periportal recruitment of inflammatory cells or fibrosis.…”
Section: Effect Of Food Azo Dyes On Liver Enzymes and Hepatotoxicitymentioning
confidence: 99%
“…Colour in the form of powder, pastes or semi fluid is added in a wide variety of food items like beverages, baking flavors, candies and other food items to improve appearance, attractiveness and taste [1,2]. These colors are able to influence or stimulate appetite, giving the consumer a quality perception [3].…”
Section: Introductionmentioning
confidence: 99%